The Challenges of Civil Society for Peace Organization CAP in Strengthening Civil Society In Southern Thailand - Budiman, Novi; Abu, Hafeez; Deswita, Deswita (State Islamic Institute of Kudus (IAIN Kudus), 2024)
This study aims to describe the challenges of the Civil Society Assembly for Peace (CAP) in strengthening civil Society in realizing Peace in southern Thailand. The method used in this research is descriptive-analytic qualitative. This study uses two sources of data, particularly primary data obtained through interviews with informants related to the problem under study and secondary data from documents, books, articles, journals, and other sources to support this research. The results showed that the purpose of the Civil Society Assembly for Peace (CAP) to unite the direction of the struggle of community organizations in realizing Peace in Southern Thailand has led to significant results. This has been proven since it was founded in 2020; as many as 27 civil society organizations have joined the civil society assembly for Peace (CAP). This Organization has received full support from various elements of the minority Muslim community in Southern Thailand. On the other hand, the Thai government considers this Organization a threat that can disrupt national political stability. Various endeavors to confine the movement of this Organization were accomplished by the Thai government in multiple ways, both in the form of physical (arrest) and non-physical actions (limiting cooperation with various organizations outside Thailand).